Anti-idiotypic antibodies specific to steroid hormones and proliferative activity of tumor in breast cancer patients - A. N. Glushkov; E. G. Polenok; S. A. Mun; L. A. Gordeeva; A. V. Antonov; P. V. Bairamov; N. E. Verzhbitskaya; G. I. Kolpinsky (Медицинская иммунология)
Nongenomic effects of antibodies specific to membrane steroid receptors are well known. Autoantibodies against estrogen receptor (ER) were revealed in blood serum of breast cancer patients (BCP). Their serum levels correlated with Ki-67, a protein tumor proliferation marker,. Purified antibodies stimulated in vitro proliferation of cultured MCF-7 tumor cells. Antiidiotypic antibodies against monoclonal antibodies, specific to estradiol, showed similar agonist activity. However, the function of auto-antibodies against progesterone receptor (PR) remained unknown. The purpose of this study was to search for an association between serum antiidiotypic antibodies specific to estradiol and progesterone (IgG2-E2 and IgG2-Pg), and expression of Ki-67 tumor protein in BCP. The IgG2-E2 and IgG2-Pg were studied in 204 healthy women and 663 BCP with ER+/PR+ tumors using ELISA technique with adsorbed monoclonal antibodies against E2 and Pg. Ki-67, ER and PR were detected by immunohistochemical methods. High levels of IgG2-E2 in stage I BCP were detected more frequently than in healthy women (63.9% vs 40.2%, р < 0.001), being more common in cases with Ki-67 > 14, than with tumors with Ki-67 ≤ 14 (63.9% vs 56.9%, р = 0.03). Similar association of IgG2- Pg with Ki-67 was not revealed. The individually low levels of both IgG2-E2 and IgG2-Pg in stage I BCP with Ki-67 ≤ 14 tumors were found in 55.2%, compared to 22.4% in cases with Ki-67 > 30. The cooperatively high IgG2-E2 and IgG2-Pg levels were detected in 35.7% of stage I BCP with Ki-67 ≤ 14 tumors and in 28.6% with Ki-67 > 30 cases (p = 0.03). On the contrary, high IgG2-E2 levels in BCP II-IV stages with tumor Ki-67 > 30 were less comon, than with Ki-67 ≤ 14 (49.1% vs 64.2%, р = 0.03). Similar association was found with IgG2-Pg (47.2% vs 62.2%, р = 0.03). The cooperatively high individual IgG2- E2 and IgG2-Pg levels were detected in BCP at II-IV stages with Ki-67 ≤ 14 and Ki-67 > 30 (respectively, 38.0% and 37.0). These indices comprised 21.5% and 53.9% when the levels of studied antibodies were low (p = 0.003). In conclusion, high individual levels of both IgG2-E2 and IgG2-Pg were associated with high proliferative activity of ER+/PR+ breast cancer at initial tumor growth (stage I), and with low proliferation rates at subsequent tumor growth (stages II-IV).